Influences of tropical Pacific and North Atlantic SST anomalies on summer drought over Asia - Zhang, Jianmin; Wu, Renguang; Gu, Qinlu; Chen, Xinhai; Jia, Xiaojing; Zhang, Yanting (Climate dynamics, 2023)
Present study investigates the characteristics and factors of summer drought variations over Asia during 1950–2020 using 3-month Standardized Precipitation Evapotranspiration Index (SPEI03) in July. The leading mode of Asian summer drought variations exhibits a roughly north–south contrasting distribution across 30° N with dominant interannual variability. The interannual variation of the leading mode is associated with both precipitation and temperature. In comparison, the contribution of precipitation is larger in the eastern part of the mid-latitude Asia. The Asian summer drought variations subject to both individual and combined impacts of preceding winter equatorial central-eastern Pacific (ECEP) sea surface temperature (SST) anomalies and concurrent North Atlantic (NA) tripole SST anomalies. Preceding ECEP SST anomalies induce anomalous vertical motion and precipitation over the mid-latitude Asia through large-scale divergence and convergence in previous winter and spring. The resulted soil moisture anomalies persist to summer and are conducive to anomalous summer precipitation through evaporation. The accompanying changes in cloud-radiation, surface longwave radiation and sensible heat flux induce temperature and evapotranspiration anomalies. The NA tripole SST anomalies induce anomalous vorticity forcing over the western mid-latitude NA. This contributes to a wave train that propagates from the NA to East Asia and affects wind and vertical motion over the mid-latitude Asia.